PECULIARITIES OF DOG TOXASCAROSIS SPREADING IN THE TOWN OF POLTAVA - Yevstafieva, V. О.; Golofayev, B. Yu. (Scientific Progress & Innovations, 2019)
At present dog breeding is becoming important in different branches of the economy. The requirements in the development of utility, decorative, sports, and special dog breeding are increasing, because these ani-mals are indispensable assistants of people. There are a lot of various forms of using dogs in the world, one of which is to enrich the human spiritual experience. Besides, dogs are used in protecting economic and oth-er objects, defending state borders. The interest in dog breeding leads to gathering a great number of dogs on a limited territory, and common walking dogs results in considerable spreading of invasion diseases, in particular, animal digestive tract nematodoses. Dog toxascarosis is considered by scholars to be one of the most widely spread dog helminthoses. The research was conducted in the laboratory of the Department of parasitology and veterinary-sanitary expert examination at Poltava State Agrarian Academy. The aim of the investigation was to study the peculiarities of spreading dog toxascarosis in the town of Poltava taking into account the dependence of infestation indices on the age of animals, and also the peculiarities of the disease course in case of dog digestive tract mixed invasions. As a result of coproscopical examination it was estab-lished that dog toxascarosis is a spread invasion on the territory of Poltava, and its average prevalence is 31.25 %. It was found out that dog toxascarosis mainly takes its course as mono-invasion (75 %). Mixed in-vasions were revealed in 25 % of animals suffering from toxascarosis, where Toxascaris leoninа were found together with intestinal nematodes of Trichuris vulpis, Uncinaria stenocephala species and protozoa of Isospora canis species. Two-component mixed invasions were revealed in 70 % and three-component – in 30 % of cases. Most often dog toxascarosis-trichurosis associated invasion was diagnosed (40 % of the total number of the dogs suffering from mixed invasion). More rarely toxascarosis-uncinariosis (20 %), toxascar-osis-trichurosis-uncinariosis (20 %), toxascarosis-isosporosis, and toxascarosis-trichurosis-isosporosis as-sociated invasions (each 10 % respectively) were found. It was determined that toxascarosis invasion preva-lence indices depend on the age of dogs. So, young dogs aged from 6 to 12 months were infested with T. leoninа most of all, where average prevalence reached 46.51 %. The lowest prevalence indices were reg-istered in dogs older than five years (16.67 %). The obtained results of the research will enable to increase the effectiveness of conducting treatment and prevention measures in case of dog toxascarosis taking into account the peculiarities of the course and dynamics of the invasion.